2015
DOI: 10.1371/journal.pone.0121292
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Enucleation Techniques and Materials for Treatment of Retinoblastoma: An International Survey

Abstract: PurposeTo investigate the current practice of enucleation with or without orbital implant for retinoblastoma in countries across the world.MethodsA digital survey identifying operation techniques and material used for orbital implants after enucleation in patients with retinoblastoma.ResultsWe received a response of 58 surgeons in 32 different countries. A primary artificial implant is routinely inserted by 42 (72.4%) surgeons. Ten (17.2%) surgeons leave the socket empty, three (5.2%) decide per case. Other su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 31 publications
(33 reference statements)
1
31
0
4
Order By: Relevance
“…Many different reconstruction techniques are used worldwide. 139 Comparative studies have shown best artificial eye motility with a simple, cheap, polymethyl methacrylate implant and muscles sutured to the conjunctiva to form the pockets to hold the artificial eye (myoconjunctival approach), which is affordable world-wide. 140,141 Porous implants that become vascularized with muscles sutured to the implant are commonly used but are susceptible to infection and extrusion, and are more costly.…”
Section: Managementmentioning
confidence: 99%
“…Many different reconstruction techniques are used worldwide. 139 Comparative studies have shown best artificial eye motility with a simple, cheap, polymethyl methacrylate implant and muscles sutured to the conjunctiva to form the pockets to hold the artificial eye (myoconjunctival approach), which is affordable world-wide. 140,141 Porous implants that become vascularized with muscles sutured to the implant are commonly used but are susceptible to infection and extrusion, and are more costly.…”
Section: Managementmentioning
confidence: 99%
“…In our cohort, dehiscence of the aponeurosis causing the ptosis is most likely. In this cohort, the four rectus muscles were sutured to donor sclera at the anterior site of the implant with the corners attached to each other (Mourits et al 2015). The larger the implant, the more the muscles have to be stretched forward to reach this position.…”
Section: Discussionmentioning
confidence: 99%
“…The latter should be tested in a prospective study. Proposed options are more posterior positioning of only the rectus superior as mentioned but not published by colleagues (Mourits et al 2015). We do however wonder how much posteriorly this should be and whether the implant would not tilt as the other muscles will deliver an unequal amount of tension.…”
Section: Discussionmentioning
confidence: 99%
“…A special mention should be dedicated to the "quasiintegrated" implant, which was introduced in the 1970s and was characterized by a "lock-and-key" coupling system to better support the external ocular prosthesis and expand its range of movements. 22,23 Exposure in porous implants can be treated with conservative management using pharmacological treatment or salvage strategies (anterior apposition of scleral or polymeric patches), without the need for implant removal and replacement with a new one. 20 The mounds created two perpendicular channels so that the stumps of horizontal and vertical extraocular muscles could be sutured together before being covered by the conjunctiva.…”
Section: Introductionmentioning
confidence: 99%